PENERAPAN APLIKASI KONSELING PENYAKIT DIARE KLINIK SANITASI DI PUSKESMAS - Trisfa Augia; Hendery Dahlan (HUMAN CARE JOURNAL, 2020)
Diarrheal disease is an environmental-based disease that is still a public health problem in Indonesia due to it is a major contributor to the death of children, especially children under five. This disease is expected to be prevented through optimal counseling efforts at the public health center. However, human resources and limited time are major issues that cause counseling activities still not optimal. Therefore, an android-based diarrhea counseling application was developed using Kobo ToolBox®. This study aims to determine the accessibility, effectiveness, and efficiency of the application in conducting counseling, particularly identifying problems and recommendations for patients. The research method used descriptive quantitative method and was carried out in two health centers in Padang. The results of this study note that 88.89% of respondents expressed this application was easily accessed and can be used offline or online, 82.22% of respondents said this application was easy to operate and helped the implementation of counseling, 93.33% agreed this application requires a short time, the contents of the application referred to regulations, and questions and application menus are easy to understand and 96.67% of respondents said the application display was by needs. It can be concluded that this application helps health workers in conducting diarrhea counseling and is expected to be developed for other environmental-based diseases